Call me princess - Blaedel, Sara. (New York : Gallery Books, 2012)
Copenhagen Detective Inspector Louise Rick searches for an online predator who has brutally attacked a young woman in her home, a crime that prompts Louise to set up an online profile on the dating site where the predator is soliciting women.
Keywords: Policewomen -- Fiction; Detectives -- Denmark -- Fiction; Online sexual predators -- Fiction; Murder -- Investigation -- Fiction; Copenhagen (Denmark) -- Fiction; Mystery fiction